Orchestration of reading and writing activities and response journal outputs - Chiu, Menelea Mutuc (2007)
The primary concern of the study was the examination of the influence of the participants' orchestration, or the temporal decisions made by individuals as they read and write, on the quality of their written output. Fifty-three freshmen college student participants were asked to read 9 texts: 3 poems, 3 journalistic essays, and 3 academic texts. An attitudinal survey was employed. Results showed that reading and writing orchestration have a significant positive influence on attitude and quality of the participants' journal outputs. Text types also have a significant influence on the linguistic quality of the output. It was recommended that independent or autonomous reading and writing activities be promoted in the classrooms and included in the consideration for syllabus/curriculum design, and teacher education programs.